A hexa-quinoline based C3-symmetric chemosensor for dual sensing of zinc(ii) and PPi in an aqueous medium via chelation induced "OFF–ON–OFF" emission. Issue 19 (4th May 2018) - Sinha, Sanghamitra; Chowdhury, Bijit; Adarsh, Nayarassery N.; Ghosh, Pradyut
Abstract : "OFF–ON–OFF" luminescence switching behavior of a hexa-quinoline based sensor towards Zn 2+ and PPi in an aqueous buffer medium is demonstrated. Abstract : A quinoline-based C 3 -symmetric fluorescent probe (1 ), N, N ′, N ′′-((2, 4, 6-trimethylbenzene-1, 3, 5-triyl)tris(methylene))tris(1-(quinolin-2-yl)- N -(quinolin-2-ylmethyl)methanamine), has been developed which can selectively detect Zn 2+ without the interference of Cd 2+ via significant enhancement in emission intensity (fluorescence "turn-ON") associated with distinct fluorescence colour changes and very low detection limits (35.60 × 10 −9 M in acetonitrile and 29.45 × 10 −8 M in 50% aqueous buffer (10 mM HEPES, pH = 7.4) acetonitrile media). Importantly, this sensor is operative with a broad pH window (pH 4–10). The sensing phenomenon has been duly studied through UV-vis, steady-state, and time-resolved fluorescence spectroscopic methods indicating 1 : 3 stoichiometric binding between1 and Zn 2+ which is further corroborated by 1 H NMR studies. Density functional theoretical (DFT) calculations provide the optimized molecular geometry and properties of the zinc complex, 1 [Zn(ClO4 )]3 3+, which is proposed to be formed in acetonitrile. The results are in line with the solution-state experimental findings. The single crystal X-ray study provides the solid state structure of the trinuclear Zn 2+ complex showing solubility in an aqueous buffer (10 mM HEPES, pH = 7.4). Finally, the resulting trinuclear Zn 2+ complex has been utilized as a fluorescence "turn-OFF" sensor for the selective detection of pyrophosphate in a 70% aqueous buffer (10 mM HEPES, pH = 7.4) acetonitrile solvent with a nanomolar detection limit (45.37 × 10 −9 M).